2017
DOI: 10.1016/j.jana.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Mental Health and HIV Services in Zimbabwean Communities: A Nurse and Community-led Approach to Reach the Most Vulnerable

Abstract: Alcohol use and depression negatively impact adherence, retention in care, and HIV progression, and people living with HIV (PLWH) have disproportionately higher depression rates. In developing countries, more than 76% of people with mental health issues receive no treatment. We hypothesized that stepped-care mental health/HIV integration provided by multiple service professionals in Zimbabwe would be acceptable and feasible. A three-phase mixed-method design was used with a longitudinal cohort of 325 nurses, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Recent reviews have identified the need for integrating mental health services into HIV care in high-burden settings [29], especially for adolescents [7]. Integrated models, which might consist of multidisciplinary teams coordinating care in a "one-stop shop", or service providers managing two-way referrals between HIV and mental health care, have been found to be both feasible and acceptable in high-burden, low-resource settings [30,31].…”
Section: Invest In High-quality Research To Test the Effectiveness mentioning
confidence: 99%
“…Recent reviews have identified the need for integrating mental health services into HIV care in high-burden settings [29], especially for adolescents [7]. Integrated models, which might consist of multidisciplinary teams coordinating care in a "one-stop shop", or service providers managing two-way referrals between HIV and mental health care, have been found to be both feasible and acceptable in high-burden, low-resource settings [30,31].…”
Section: Invest In High-quality Research To Test the Effectiveness mentioning
confidence: 99%
“…Among these factors, HIV is regarded as one of major factors contributing to an increase in mental disorders. According to Duffy et al [5], people living with HIV are more than twice as likely to experience a mental health disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Although all these factors are in conformity with what other studies have found, contextualization is very important in order to address them. Poor or low accessibility of care for patients with mental health problems may have been cited by various researchers, [7,[36][37][38][39][40][41][42][43] however, the contexts within which these constraints occur are unique to communities and should not be looked at in isolation. In this study, low financial resources, difficult geographical terrain, and family indifferences towards mental illness compounded and contextualized the challenge of low accessibility of mental healthcare services in rural Mbarara district.…”
Section: Discussionmentioning
confidence: 99%